Imatinib treatment of paediatric Philadelphia chromosome-positive acute lymphoblastic leukaemia (EsPhALL2010): a prospective, intergroup, open-label, single-arm clinical trial. Issue 12 (December 2018) - Biondi, Andrea; Gandemer, Virginie; De Lorenzo, Paola; Cario, Gunnar; Campbell, Myriam; Castor, Anders; Pieters, Rob; Baruchel, André; Vora, Ajay; Leoni, Veronica; Stary, Jan; Escherich, Gabriele; et al.
Summary: Background: The EsPhALL2004 randomised trial showed a 10% advantage in disease-free survival for short, discontinuous use of imatinib after induction compared with no use of imatinib in patients with Philadelphia chromosome-positive acute lymphoblastic leukaemia receiving Berlin-Frankfurt-Münster chemotherapy and haemopoietic stem-cell transplantation (HSCT). Other contemporary studies showed an advantage from continuous protracted exposure to imatinib, challenging the indications to transplant. The EsPhALL2010 study was designed to assess whether imatinib given from day 15 of induction and continuously throughout chemotherapy led to a different outcome to that obtained in EsPhALL2004, despite decreasing the number of patients having HSCT. Methods: This prospective, intergroup, open-label, single-arm clinical trial (EsPhALL2010) was done at 11 study groups across Europe, Chile, and Hong Kong. Patients aged 1–17 years with the translocation t(9;22)(q34;q11) who were recruited into national front-line trials for acute lymphoblastic leukaemia were eligible for this trial. Patients with abnormal renal or hepatic function or an active systemic infection were ineligible. Patients received imatinib 300 mg/m 2 continuously from day 15 of induction during chemotherapy. Eligibility to HSCT depended on early morphological response and minimal residual disease. Imatinib was recommended throughout the first year after transplant. The co-primary endpoints were event-free survival and overall survival. All analyses were done in the intention-to-treat population. The trial is registered with the European Clinical Trials Database (EudraCT 2004-001647-30) and withClinicalTrials.gov (NCT00287105 ) and is completed. Findings: 158 patients were screened for eligibility, of whom 155 were enrolled between Jan 1, 2010, and Dec 31, 2014. 151 (97%) patients achieved first complete remission after induction and four after the consolidation phase, with 102 (66%) patients categorised as good risk and 53 (34%) as poor risk according to EsPhALL risk stratification criteria. 59 (38%) patients had HSCT during their first complete remission. 40 (26%) patients relapsed and 41 (26%) patients died during the study (25 [61%] during complete continuous remission, and 16 [39%] after relapse). The 5-year event-free survival was 57·0% (95% CI 48·5–64·6) and 5-year overall survival was 71·8% (63·5–78·5). 154 serious adverse events were reported in 80 (52%) of 155 patients. The most common toxicity was infection (61 [39%] patients, mostly bacterial); gastrointestinal disorders occurred in ten (6%) patients and osteonecrosis in eight (5%). Serious adverse events occurred mainly during high-risk blocks and delayed intensifications, including 14 fatal events (one in the consolidation phase, six in high-risk blocks, six in first delayed intensification, and one in second delayed intensification). Interpretation: Although HSCT was done in a smaller proportion of patients in EsPhALL2010 than in EsPhALL2004, event-free and overall survival were similar between the two studies. Our data suggest that imatinib given early and continuously with intensive chemotherapy might increase toxicity. Funding: Projet Hospitalier de Recherche Clinique-Cancer and Novartis France; Bloodwise and Cancer Research UK; Ministry of Health, Czech Republic.